Surgical treatment of mitral stenosis, complicated by massive thrombosis of the left atrium: stationary stage - V. V. Popov; O. O. Bolshak; V. Zh. Boukarim; О. M. Gurtovenko; O. M. Trembovetska (Клінічна хірургія)
Objective. Elaboration of the correction methodology of mitral stenosis, complicated by massive thrombosis of left atrium, for improvement of immediate and late results of surgical treatment of this pathology.